Do the G20 Countries' Increased Economic Growth, Foreign Direct Investment, Industry Value-added, and Population Change Contribute to CO2 Emissions? - Rasyida Pertiwi; Imam Asngari; Vinny Dwi Melliny; Febrian; Gustriani (Department of Development Economics, Universitas Sriwijaya, 2023)
Economic development plays a crucial role in contributing to CO2 emissions. Therefore, this research aims to investigate environmental degradation caused by economic activities within the scope of G-20 Countries, which comprise the largest economies and advanced industries. The primary objective of this study is to deliver an empirical study of gross domestic product, foreign direct investment, industry value-added, and population on CO2 emissions in G20 Countries. Using panel data from 2000-2022, the research found a positive correlation between GDP and CO2 emissions. Meanwhile, by utilizing GDP squared, the existence of the Environmental Kuznet Curve (EKC) theory was identified. The EKC theory indicates a significant negative correlation between GDP squared and CO2 emission. This is attributed to several factors, including increased public awareness of environmental protection and technological advancements in developed countries, contributing to improved energy efficiency. For the variables of FDI and population, a negative correlation with CO2 was found. On the other hand, the value-added industry shows a positive and significant correlation with CO2 emissions.